APPLICATION OF GOOD GOVERNANCE IN DIRECT CASH ASSISTANCE BUDGET MANAGEMENT IN PONG LAO VILLAGE, RUTENG DISTRICT, MANGGARAI DISTRICT, 2022 - Akhmad Syafruddin (Adisam Publisher, 2025)
Direct cash assistance is a program rolled out by the government to the poor. The process of implementing aid must pay attention to the principles of good governance so that the target is right on target. This research aims to answer the question of how to apply the principles of good governance in collecting data on recipients of direct cash assistance in Pong Lao Village, Ruteng District, Manggarai Regency. The research uses a qualitative case study type method. Research informants were village staff, hamlet heads and the community. Data collection was carried out through interviews and literature study. The research results show that data collection on recipients of direct cash assistance follows procedures that prioritise people in the inferior category. Application of sound governance principles at every stage; the planning stage applies the principles of democracy and participation; the organising stage applies the principles of professionalism, efficiency and effectiveness; in the mobilisation stage, they have implemented the principle of excellent service and the principle of supremacy of law; in the supervision stage, the principles of accountability and transparency have been implemented.